Blue velvet - Lynch, David, 1946-; Caruso, Fred.; MacLachlan, Kyle, 1960-; Rossellini, Isabella; Hopper, Dennis, 1936-; Dern, Laura; Lange, Hope.; Stockwell, Dean, 1938-; Elmes, Frederick; Dunham, Duwayne; Badalamenti, Angelo; De Laurentiis Entertainment Group; et al. (Santa Monica, Calif. : MGM Home Entertainment, 2002)
A college student stumbles across a bizarre mystery and wants to know more. The strange world he's found lurking beneath his hometown picture-postcard veneer is about to become much stranger.
DVD, widescreen presentation. Dolby digital stereo surround.
In English with optional French or Spanish soundtrack; optional subtitles in English, French, Spanish or Portuguese.
Closed captioned.
Kyle MacLachlan, Isabella Rossellini, Dennis Hopper, Laura Dern, Hope Lange, Dean Stockwell.
Director of photography, Frederick Elmes ; editor, Duwayne Dunham ; music, Angelo Badalamenti.
Originally produced as a motion picture in 1986.
Keywords: Criminal investigation -- Drama; Sexual deviation -- Drama; Perversiones sexuales -- Teatro; Investigaciâon (Pesquisas) -- Teatro; Feature films; Detective and mystery films; Video recordings for the hearing impaired; Videos (DVD)